A comparison of feeding hay to heifers on bluestem pasture and in drylot - Smith, E.F.; Good, D.L.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This study was designed to evaluate mature dry winter pasture for animals fed all of the harvested roughage such as hay that they would consume. In addition one group animals wintered in drylot were moved to pasture one month prior to the start of the summer growing season to study their adjustment to pasture.
Keywords: Beef; Heifers; Bluestem pasture; Drylot